A Stick, a Sparrow, a Kettle. The Non-Human Cosmos by Witold Gombrowicz: Between the Pre- and Meta-Pre-Posthumanistic Approach to the Problem: Between the Pre- and Meta-Pre-Posthumanist Approach to the Problem. - Gosk, Hanna (Porównania, 2021)
The text proposes a rereading of Witold Gombrowicz’s Kosmos (1965) in the posthumanist perspective. It puts forth a thesis that the novel contains pre- and, in a way, meta-posthumanist features, and, through them, it problematizes this way of perceiving reality. The article proposes to look at the narrator’s message as at a “report” on an experiment that has turned out to be not quite successful, but opening a new, tempting perspective. In this experiment human subject is situated in a world in which things perceived by him and real things turn out to be “for a while” (or maybe since forever) parts of the same universe without form or content, interior or exterior, not succumbing to hierarchization in categories of subordination or superiority, almost equally endowed in the power of agency, if by this we mean setting the world in motion (in the sense-creating meaning).